Molecular basis of biotic and abiotic stress management attributes of plant growth promoting rhizobacteria - Jain, Tripta; Gehlot, Pushpa; Yadav, Jyoti; Chittora , Deepali (Journal of Postharvest Technology, 2023)
Food scarcity is becoming a global issue as the world’s population grows. New agricultural strategies that help enhance agricultural crop production and productivity are urgently needed to meet the growing food demand of the world’s population. There are various stresses prevalent that prominently reduce the plant productivity. These stresses can be either biotic or abiotic. To ensure food supply to growing population worldwide, the damage caused by these stresses should be minimized. Plant growth promoting rhizobacteria (PGPR) are root colonizing non-pathogenic bacteria, which found surrounding the roots and have beneficial effects on growth of plant. PGPR act as a source of hormones, vitamins and growth factors that enhance plant growth and yield. PGPR could be a alternative tool for sustainable agriculture as they can induce resistance against various biotic and abiotic stresses. Some PGPR increases tolerance against abiotic stresses like drought, salinity, temperature, oxidative stress, nutrient deficiency and metal toxicity. Several activities of PGPRs such as production of antibiotic compounds, bacteriocins, synthesis and secretion of cell wall degrading enzymes, induction of systemic resistance (ISR) and production of volatile organic compounds are effective in control of many biotic stresses such as plant pathogens. Several PGPR strains such as Pseudomonas spp., Bacillus spp. are proved to be an effective biocontrol agents against plant pathogens. This review emphasized on the role of PGPR for management of various biotic and abiotic stress.